EFFECT OF COMMERCIAL RATION REPLACEMENT WITH BREAD WASTE ON KAMPUNG UNGGUL BALITNAK (KUB) CHICKEN FARM’S INCOME - H., Kurniawan; Putri, B. R. T.; Siti, N. W. (Jurnal Peternakan Tropika, 2023)
This study aims to determine kampung unggul balitnak (KUB) chicken farm’s income was given a ration containing bread waste. The study was carried out for eight weeks in the Reseach Farm at Banjar Ulun Uma, Gulingan Village, Mengwi District, Badung Regency, Bali. The design used in this reaseach is completely randomized design (CRD) consisting of 3 treatments and 5 replications, each  using 2 chickens, so the total number of chickens per treatment is 10. The treatments were 100% commercial ration (P0), 75% commercial ration + 25% bread waste from commercial ration (P1), 50% of commercial ration + 50% of bread waste from commercial ration (P2). The observed variables include income analysis based on costs, revenues, income, R/C ratio and BEP. The results of the income analysis showed that KUB chickens with 50% commercial ration + 50% bread waste gave the best results farmer’s income Rp. 411.325,-/period, R/C ratio 1.890, BEP production unit is 4.61 kg of whole chiken meat the BEP of the selling price of KUB chickens/kg is Rp. 44,154,-/kg whole chiken meat, and BEP revenue  Rp. 253,742,-/period. Based on the results of the study, it can be concluded that replacement of commercial rations with 50% bread waste will increase farmer’s income for 37,41% compared to the P0 treatment.   Keywords: Income Analysis, KUB chicken, Bread waste.